2019
DOI: 10.1007/s40279-019-01095-9
|View full text |Cite
|
Sign up to set email alerts
|

Reliability, Validity and Utility of Inertial Sensor Systems for Postural Control Assessment in Sport Science and Medicine Applications: A Systematic Review

Abstract: Background: Recent advances in mobile sensing and computing technology has provided a means to objectively quantify postural control in unobtrusive environment. This has resulted in the rapid development and evaluation of a series of wearable inertial sensor-based assessments. However, the validity, reliability and clinical utility of such systems is not fully understood. Objectives: This systematic review aims to synthesise and evaluate studies which have investigated the ability of wearable inertial sensor s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 74 publications
0
39
0
1
Order By: Relevance
“…Although several systematic reviews already available in literature demonstrated the reliability, validity, and utility of inertial sensors for sport applications [8,143,144], an overview on specific applications that can be implemented by analysing kinematics, kinetics, muscle activity, and physiological parameters through wearable sensors is missing. From this perspective, we aimed to provide an overview on applications of sport biomechanics that require the use of wearable sensors, not only the inertial ones.…”
Section: Introductionmentioning
confidence: 99%
“…Although several systematic reviews already available in literature demonstrated the reliability, validity, and utility of inertial sensors for sport applications [8,143,144], an overview on specific applications that can be implemented by analysing kinematics, kinetics, muscle activity, and physiological parameters through wearable sensors is missing. From this perspective, we aimed to provide an overview on applications of sport biomechanics that require the use of wearable sensors, not only the inertial ones.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in smart-phone and wearable technology has allowed for the development of digital health systems capable of objectively quantifying human movement [13,14]. Such systems have overcome some of the limitations typically seen with traditional biomechanical measurement tools (force platforms and marker-based motion capture), allowing for the quantification of clinical balance assessments [15]. The Ybalance test (YBT) is one of the most commonly used sports medicine dynamic balance assessments, providing a means to validly and reliably quantify sensorimotor function [16].…”
Section: Introductionmentioning
confidence: 99%
“…The sports technology and wearables industry has provided opportunity to collect an almost endless stream of data regarding athlete health and performance; however, with the huge amount of data that can be accessed and used, there are also issues that must be dealt with. For example, despite the popularity of novel technologies and wearables, very few of these devices have been rigorously and independently examined to determine their accuracy, reliability, validity (Johnston et al, 2019), and overall usefulness within sports medicine and performance settings or populations (Wallen et al, 2016, MacDonald et al, 2017.…”
Section: Modern Approachesmentioning
confidence: 99%